Analisis Kualitas Pelayanan Dengan Menggunakan Metode Fuzzy Servqual - Kecitaan Harefa (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
Bank Rakyat Indonesia is a leading bank that can reach customers in all corners of the country, designed to expand banking services that change all customers, especially customers who have limited access not having to go to branches and work units to make transactions, but can be done through BRILink agents. BRILink is a BRI service in which BRI works together with BRI customers as an agent who can offer online banking transactions in real time to the public using the BRI EDC Mini ATM with a profit sharing concept. BRILink is the executor of the clever behavior program by Bank Rakyat Indonesia based on OJK regulations, namely an officeless financial transaction service program through bank agent intermediaries. The purpose of this study is to apply the fuzzy service quality (servqual) method in improving service, so as to provide service satisfaction to BRILink agent customers Enoni Meruyung with research stages consisting of needs analysis, data collection, data processing and analysis, implementation of fuzzy service quality testing (servqual), and analysis of the results. After processing the data on each dimension, there is an Emphaty (Caring) dimension in the first place with a gap value of 0.633, the Assurance dimension in the second order with a gap value of 0.510, the Responsiveness dimension in third place with a gap value of - 0.343, the Tangible dimension (Physical Evidence) is in fourth place with a gap value of -0.606 and the Reability dimension is in fifth position with a gap value of -0.684.